Study on Track to Earth Insulation Defect Fault Location Method in Urban Mass Transit - LI Guo-xin; ZHANG Dong-liang; WU Yu-ling; LIAO Hong-mei (Institute of Advanced Engineering and Science, 2012)
With the urban mass transit operating, due to the impact of natural and human factors, track to earth insulation defect will occur. Keeping track to earth resistance is an effective method of preventing stray current. When track to earth insulation defect occurs, the track to earth potential of the point will be nearly changed to zero. We present the track to earth insulation defect fault location method based on the feature. And the method was simulated and analyzed, the results show the fault location method is effective. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1275